2003
DOI: 10.1046/j.1365-3083.2003.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Apoptotic K562 Leukaemia Cells by Immature Dendritic Cells is Greatly Facilitated by Serum

Abstract: Dendritic cells (DCs) are potent antigen-presenting cells and play an important role in T-cell-mediated immunity. DCs have been shown to induce strong antitumour immune responses both in vitro and in vivo. One way of providing the DCs with all relevant tumour antigens would be to incubate the DCs with material from dead tumour cells. We have examined the uptake of apoptotic and necrotic K562 leukaemia cells by DCs under different culture conditions. Results from coincubation experiments strongly suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…concentration of 15 M for 10 min. Apoptosis was induced as described previously [25]. Briefly, a combination of the specific BCR-ABL tyrosine kinase inhibitor CGP 57148 (STI 571; kindly provided by Dr. Elisabeth Buchdunger, Novartis Pharma AG, Basel, Switzerland) and ␥ irradiation was used.…”
Section: Uptake Of Apoptotic K562 Leukemia Cells By Imodc and Pbdcmentioning
confidence: 99%
See 1 more Smart Citation
“…concentration of 15 M for 10 min. Apoptosis was induced as described previously [25]. Briefly, a combination of the specific BCR-ABL tyrosine kinase inhibitor CGP 57148 (STI 571; kindly provided by Dr. Elisabeth Buchdunger, Novartis Pharma AG, Basel, Switzerland) and ␥ irradiation was used.…”
Section: Uptake Of Apoptotic K562 Leukemia Cells By Imodc and Pbdcmentioning
confidence: 99%
“…One strategy is to load DC with material from apoptotic or necrotic tumor cells [2]. We have previously examined uptake of apoptotic and necrotic K562 leukemia cells by iMoDC [25]. Here, we have investigated the uptake of apoptotic and necrotic K562 leukemia cells by PBDC using the uptake by iMoDC as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…20 Other studies reported that the serum concentration of culture media can also influence CD1a ϩ and CD1a Ϫ dichotomy and modify the functional properties of these DC subsets. [21][22][23] The nature of exogenous factors or regulatory pathways that may modulate the ratio of CD1a ϩ and CD1a Ϫ moDCs has not been identified.…”
Section: Introductionmentioning
confidence: 99%